2014
DOI: 10.1007/s00464-014-3746-9
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of prophylactic IVC filters in gastric bypass surgery

Abstract: It is estimated that 55 % of bariatric surgeons use IVCF in high-risk patients. Prospective research that supports the use of IVCF is very limited, and individualized placement relies on retrospective studies only. In addition, patient characteristics associated with high risk vary between different studies. Our review showed that most of the published studies support the use of prophylactic IVCF and found it to be safe. On the other hand, the largest and most recent retrospective cohort study does not support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The use of inferior vena caval filters (VCFs) for prevention of PE in bariatric surgery has been evaluated in several studies, most of which were retrospective or registry studies with many differences between the VCF and non-VCF groups that likely confounded the findings. 39 Some of these studies found higher rates of DVT but similar rates of PE in the VCF groups, which might suggest a possible benefit of VCFs in preventing PE in high-risk patients. Alternatively, the higher rates of DVT might indicate that VCFs increase the risk of postoperative lower extremity venous thrombosis.…”
Section: Warfarinmentioning
confidence: 87%
“…The use of inferior vena caval filters (VCFs) for prevention of PE in bariatric surgery has been evaluated in several studies, most of which were retrospective or registry studies with many differences between the VCF and non-VCF groups that likely confounded the findings. 39 Some of these studies found higher rates of DVT but similar rates of PE in the VCF groups, which might suggest a possible benefit of VCFs in preventing PE in high-risk patients. Alternatively, the higher rates of DVT might indicate that VCFs increase the risk of postoperative lower extremity venous thrombosis.…”
Section: Warfarinmentioning
confidence: 87%
“…The more recent development of a retrievable filter has encouraged the use of IVCF as these devices are easier to insert and can subsequently be removed [7,8]. Although the currently accepted clinical practice is to use IVCF only in patients with a contraindication for anticoagulation therapy [2], several studies have reported the efficacy of prophylactic IVCF in patients at high risk of VTE [36]. Wilhelm et al [3], published a systemic review of 8 retrospective studies on the efficacy of prophylactic IVCF insertion prior to bariatric surgery (gastric bypass) and concluded that the incidence of PE in patients without pro-phylactic IVCF was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Although the currently accepted clinical practice is to use IVCF only in patients with a contraindication for anticoagulation therapy [2], several studies have reported the efficacy of prophylactic IVCF in patients at high risk of VTE [36]. Wilhelm et al [3], published a systemic review of 8 retrospective studies on the efficacy of prophylactic IVCF insertion prior to bariatric surgery (gastric bypass) and concluded that the incidence of PE in patients without pro-phylactic IVCF was higher. Decousus et al [6] also reported from a randomized trial that there are initial beneficial effects of prophylactic IVCF on the prevention of acute PE in high-risk patients with a proximal DVT, although there was the observed excess rate of recurrent DVT in permanent IVCF (PREPIC study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The combination of newer generation retrievable filters and ease of insertion has led to a huge increase in the use of IVC filters, and currently an estimated one in eight patients with documented venous thromboembolism (VTE) receives an IVC filter as part of early treatment, 6 while an additional 20% of all IVC filters are placed prophylactically in patients without VTE, such as preoperatively or in the setting of trauma. 7,8 Accompanying this increase in insertion is a concern about the lack of retrieval and the subsequent possibility for the complications of long-term implantation such as DVT, filter fracture, filter migration, and caval occlusion.…”
mentioning
confidence: 99%